2016
DOI: 10.1007/s40333-016-0010-2
|View full text |Cite
|
Sign up to set email alerts
|

Soil hydraulic conductivity as affected by vegetation restoration age on the Loess Plateau, China

Abstract: Abstract:The Loess Plateau of China has experienced extensive vegetation restoration in the past several decades, which leads to great changes in soil properties such as soil bulk, porosity, and organic matter with the vegetation restoration age. And these soil properties have great effect on the soil infiltration and soil hydraulic conductivity. However, the potential changes in soil hydraulic conductivity caused by vegetation restoration age have not been well understood. This study was conducted to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 43 publications
2
16
3
1
Order By: Relevance
“…The effect of OMC on permeability was less pronounced, Spearman's correlation coefficient was negative and amounted to -0.54 (Table 2). The performed statistical analysis showed that the mineralization of organic matter in the studied soils resulted in an increase in permeability, which is in agreement with the findings of Zeitz and Velty (2002) but in contrast with the work of Zongping et al (2016).…”
Section: Resultssupporting
confidence: 87%
“…The effect of OMC on permeability was less pronounced, Spearman's correlation coefficient was negative and amounted to -0.54 (Table 2). The performed statistical analysis showed that the mineralization of organic matter in the studied soils resulted in an increase in permeability, which is in agreement with the findings of Zeitz and Velty (2002) but in contrast with the work of Zongping et al (2016).…”
Section: Resultssupporting
confidence: 87%
“…The rapid expansion of forest land reflects the success of ecological restoration programmes, and the expansion of orchards and construction land reflect rapid economic development. Severe soil and water losses in this area have placed enormous pressure on social and economic development 51 . The rapid development of the economy has led to rapid urbanization 52 ; hence, although the construction land area occupies a very small proportion of the study area, an obvious growth trend was evident.…”
Section: Discussionmentioning
confidence: 99%
“…In the different parts (summit, backslope and footslope) of each plot, the morphological features of vegetation were investigated based on standard individual measurements in the field (Puigdefabregas, ). Specifically, biomass (BM, g m ‐2 ) and plant coverage (PC, %) were measured by weighing standard samples (selected by the average standard tree method) and photo analysis in the field, respectively (Ren et al ., ). Botanical water storage capacity per unit of biomass (WSC, g g ‐1 ) was measured by soaking samples (selected by average standard tree method) in distilled water for 12 h and weighing (Brandt, ; Yu et al ., ).…”
Section: Methodsmentioning
confidence: 99%